BENTUK DAKWAAN IDEAL PADA KASUS TINDAK PIDANA MANIPULASI INFORMASI ELEKTRONIK BERBENTUK AKUN PALSU DI MEDIA SOSIAL(STUDI KASUS PUTUSAN NOMOR 1739/PID.SUS/2020/PN JKT.BRT) - Michelle Rezky (2022)
Nowadays there are often cases where there are irresponsible individuals who create social media accounts using other people's personal identities as if the account is the original account of the person whose identity is being used, hereinafter referred to as fake social media accounts. Such actions can be threatened with Article 35 jo. Article 51 paragraph (1) of Law Number 11 of 2008 concerning Information and Electronic Transactions (UU ITE) for criminal acts of electronic information manipulation. The type of research used by the author in this study is a prescriptive normative law research with a statute approach, a case approach, and a conceptual approach. In Verdict Number 1739/Pid.Sus/2020/PN Jkt.Brt, the defendant was declared guilty of committing a crime in Article 28 paragraph (1) jo. Article 45A paragraph (1) UU ITE. Not only fulfilling the elements in Article 28 paragraph (1) of the ITE Law, but the defendant also fulfilled the elements in Article 35 of the ITE Law. However, the defendant was not found guilty of a criminal offense under Article 35 of the ITE Law, even though Article 35 of the ITE Law was one of the prosecution's indictments. Based on this research, the form of the indictment in Verdict Number 1739/Pid.Sus/2020/PN Jkt.Brt is less precise because the form of indictment used by the public prosecutor is an alternative indictment where ideally the public prosecutor ought to uses cumulative charges because the defendant commits concursus realist crimes